An in vitro comparison of standard cleaning to a continuous passive disinfection cap for the decontamination of needle-free connectors - Anna L. Casey; Tarja J. Karpanen; Peter Nightingale; Tom S. J. Elliott (Antimicrobial Resistance and Infection Control, 2018)
Abstract Background The optimal decontamination method for needle-free connectors is still unresolved. The objective of this study was to determine if a continuous passive disinfection cap is as effective as standard cleaning for the microbial decontamination of injection ports of two types of needle-free connectors. Methods The injection ports of needle-free connectors were inoculated with Staphylococcus aureus and allowed to dry. Disinfection caps containing 70% (v/v) isopropyl alcohol (IPA) were attached to the connectors for one, three or 7 days and were compared with needle-free connectors cleaned with 2% (w/v) chlorhexidine gluconate (CHG) in 70% (v/v) IPA. The number of S. aureus remaining on the injection ports was evaluated. Median log10 reductions and 95% confidence interval (CI) were calculated and data analyzed using the Mann-Whitney test. Results The application of the disinfection cap resulted in a significantly higher reduction in S. aureus than the 2% (w/v) CHG in 70% (v/v) IPA wipe, achieving a > 5 Log10 reduction in CFU at each time point. Conclusions The disinfection caps resulted in a significantly higher reduction in S.aureus on the injection ports when compared to the use of a 2% (w/v) CHG in 70% (v/v) IPA wipe. This offers an explanation for the lower rates of central-line associated bloodstream infection (CLABSI) associated with the use of disinfection caps reported in clinical studies.